Piracy as counter-hegemony - Tanja Bosch (Communicare)
Despite several attempts by the Antipiracy Foundation in South Africa, piracy and counterfeiting of movies on DVD is still widespread. This paper explores piracy in Hanover Park, a Cape Flats township, as an expression of a politics of resistance to racism and racial disadvantage, but more specifically as a routine social practice deeply embedded within the lived reality of community members. The research questions were guided by a desire to explore qualitatively the processes by which consumers in this low-income neighbourhood practise and understand their purchase and consumption of pirated goods, particularly films on DVD. The study found that the consumers of Hanover Park engage in a complicated process of bricolage, often recontextualising what they view to communicate new meanings, appropriating African-American and gang films as a form of political cultural resistance. Because of group and familial viewing practices, social networks are solidified and piracy often becomes a form of political bricolage against a perception of racial and class marginalisation. We find that both the ‘reworking’ of community and expression of resistance unfortunately seem to occur primarily in the arena of leisure, where the practice of piracy is routinised as an integral part of the lived experiences of community members. ‘Globality’ is experienced through a preference for Hollywood and Bollywood blockbusters; and a media-saturated globalised national context meets the unequal purchasing power and economic constraints of the local context, while resulting in little moral concern over the practice of piracy, which lends a political dimension to everyday practice.